O teatro como instrumento de sensibilização ambiental: uma experiência de produção teatral da peça "Na floresta" - Godoy, Marcio Esdras de (2015)
This interdisciplinary research that unifies art and environmental education, sought, through the art of theater, analyze how it developed the piece entitled In the Forest , which began in 2010. He sought also address the development of theater production, from choosing team, actors and producers. Also explored a pedagogical aspect in the way of doing and teaching theater, from playwriting, screenwriting and preparation of actors. In the scenic development process highlights the use of recyclable materials and solid waste in the construction of scenery. Similarly, we investigated the perceptions of members committed to the solidarity project with environmental issues. Presents new opportunities for interaction design of interactive resources, and the importance played by the team involved in play with regard to the environmental situation in the Amazon. The results show the importance of theater as an educational resource, environmental awareness, vocational training and sharing group in experiments; mainly in the development process of children and adults, enabling the social inclusion of marginalized communities through reflection on the environmental problems of their daily lives.